Civic Values in Local Traditions: An Ethno Pedagogical Study of “Mepokoaso” in the Tolaki-Mekongga Community - Rahmad Rafid; Riski Febria Nurita; A. Taufiq Hidayat; Mohammad Ilham Yasin; Tati Indaryanti (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Mepokoaso is a socio-cultural practice that emphasizes the values of mutual cooperation, deliberation, solidarity, justice, and collective responsibility. These values are closely aligned with the fundamental principles of democratic citizenship, which constitute the core objectives of national character education. This study aims to identify and analyze the citizenship values embedded in the Mepokoaso tradition of the Tolaki-Mekongga community in Kolaka Regency, Southeast Sulawesi, and to explore its potential integration into Civic and Pancasila Education (PPKn) learning. The study employed a qualitative research method with an ethnopedagogical approach. Research participants included individuals and groups with direct experience, perspectives, and active involvement in the Mepokoaso cultural practice. Data were collected through literature review, in-depth interviews, and participatory observation of Mepokoaso practices in community life. Data analysis was conducted descriptively, emphasizing the substantive meanings of cultural values that are lived and sustained within the Tolaki-Mekongga community. The findings indicate that the Mepokoaso tradition functions not only as a social mechanism for conflict resolution and the strengthening of social cohesion, but also embodies essential citizenship values that can be internalized within formal education. The integration of Mepokoaso values into PPKn learning can be implemented through contextual learning approaches, classroom deliberation simulations, collaborative projects, and the development of a local-content-based curriculum.